(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Folha de S. Paulo Newspaper in the Context of Cultural and Media Industries: a Critical Look at the Headlines on Programa MaisMédicos Government Program